2005
DOI: 10.1001/archsurg.140.12.1198
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Growth of Bariatric Surgery With the Introduction of Minimally Invasive Surgery

Abstract: Hypothesis: An increase in national utilization of bariatric surgery correlates with the dissemination of laparoscopic bariatric surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
88
0
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 200 publications
(91 citation statements)
references
References 11 publications
0
88
0
1
Order By: Relevance
“…8 Advances in minimally invasive surgery have shortened recovery time, reduced peri-operative morbidity, and expanded the range of patients amenable to this procedure. 9 While previous studies have demonstrated that marked weight reduction following BAS results in a reduction in LV mass and improved diastolic filling, 10 outcomes of patients with severe systolic heart failure following BAS have not been previously reported. subsequent 12 mo.…”
Section: Introductionmentioning
confidence: 98%
“…8 Advances in minimally invasive surgery have shortened recovery time, reduced peri-operative morbidity, and expanded the range of patients amenable to this procedure. 9 While previous studies have demonstrated that marked weight reduction following BAS results in a reduction in LV mass and improved diastolic filling, 10 outcomes of patients with severe systolic heart failure following BAS have not been previously reported. subsequent 12 mo.…”
Section: Introductionmentioning
confidence: 98%
“…In 1994, Wittgrove et al [6] performed the first laparoscopic bypass in Roux-en-Y with the purpose of treating this pathology. This method, over the years, has become one of the most accomplished in the world [7], with about 140,000 procedures performed annually in the USA by the year 2008 [8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the number of patients undergoing Roux-en-Y gastric bypass (RYGB) surgery has increased by almost tenfold in the past 2 decades, with approximately 101,645 operations performed in 2011 alone [18,19]. However, although RYGB is effective for the vast majority of patients, a small proportion of RYGB patients develop serious nutritional complications, debilitating gastrointestinal (GI) symptoms, and/or fail to reach their weight loss goals [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%